2019
DOI: 10.1021/jacs.8b11371
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Ultra-Weak Protein Self-Association by Non-ideal Sedimentation Velocity

Abstract: Ultra-weak self-association can govern the macroscopic solution behavior of concentrated macromolecular solutions ranging from food products to pharmaceutical formulations and the cytosol. For example, it can promote dynamic assembly of multi-protein signaling complexes, lead to intracellular liquid–liquid phase transitions, and seed crystallization or pathological aggregates. Unfortunately, weak self-association is technically extremely difficult to study, as it requires very high protein concentrations where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 67 publications
(121 reference statements)
1
21
0
Order By: Relevance
“…Yang et al (2018) showed that increasing salt suppresses mAb association and allows k s values to increase and approach values of 10 ml/g. Recently Chaturvedi et al (2019) and Connolly et al (2012) reported k s values > 20 ml/g in low salt conditions. Many investigations vary salt concentration and observe a suppression of association and reduction in viscosity (Yadev et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al (2018) showed that increasing salt suppresses mAb association and allows k s values to increase and approach values of 10 ml/g. Recently Chaturvedi et al (2019) and Connolly et al (2012) reported k s values > 20 ml/g in low salt conditions. Many investigations vary salt concentration and observe a suppression of association and reduction in viscosity (Yadev et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally assumed that the correct concentration scale for high concentration work is volume fraction (Ross and Minton 1977) and recent AUC studies on high concentration use the volume fraction Φ scale (Chaturvedi et al 2018;Chaturvedi and Schuck 2019). The conversion is in principle a linear transformation, as simple as νc (Broide et al 1991), but more realistically V s c where the swollen or effective volume is used (Rowe 1992;Chaturvedi and Schuck 2019). At high volume fraction the shape and packing considerations may become important for mAbs (Garidel et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Use of detection at the >290 nm flank of the protein extinction should be avoided, since the extinction coefficient gradients are accompanied by degrading signal linearity (Schuck et al, 2015). Instead, one can exploit that the interference optical system offers a much wider linear concentration range and combine this with the use of shorter optical pathlength centerpieces (Chaturvedi, Sagar, Zhao, Wistow, & Schuck, 2019). 2As total protein weight concentrations exceed 1 mg/ml, nonideality has to be taken into account.…”
Section: Adjustment Of Data Acquisition and Analysis Parameters For Lmentioning
confidence: 99%
“…An advantage is that this absorbs nonideality effects, and the resulting s w -values do not need to be corrected for nonideality anymore. In the concentration series, the k S -value is typically determined from the data at the highest concentration and then fixed for all lower concentrations as described in Chaturvedi et al (2019). In this fashion, ultraweak interactions with millimolar K d -values can be studied (Chaturvedi et al, 2019).…”
Section: Adjustment Of Data Acquisition and Analysis Parameters For Lmentioning
confidence: 99%
“…32,42,43 However, none of these simple experimental methodologies are appropriate for the characterization of transient, ultraweak interactions characterized by very high dissociation constants and short residence times. Analytical ultracentrifugation constitutes a more robust and sensitive tool to investigate ultraweak biomolecular interactions, [44][45][46] but this has yet to be explored in more detail in the study of NP interactions. 31,47 While ultraweak interactions with dissociation constants in the millimolar (mM) range usually have no major impact on conventional biochemical assays performed in vitro under dilute solution conditions, they cannot be ignored in macromolecular crowded media.…”
Section: Introductionmentioning
confidence: 99%